Prevalence, risk factors and clinical profile of patients with cardioembolic stroke in South India: a five-year prospective study - Manorenj, Sandhya; Barla, Sudhakar; Jawalker, Srikant (International Journal Of Community Medicine And Public Health, 2020)
Background: Stroke is the second leading cause of mortality and morbidity worldwide. Cardioembolic stroke accounts for 15-30% of Ischemic stroke. There have been very few clinical studies on cardioembolic stroke, especially from India. Our aim was to provide a demographic, risk factor and clinical profile of patients with cardioembolic stroke in South India. Methods: A prospective study was conducted at the Neurology Inpatient Department over a period of 5 years from January 2013 to January 2018 collecting necessary information and data from all cases diagnosed as cardioembolic stroke. Results: 651 patients were diagnosed to have acute Ischemic stroke. Of the 76 patients (11.6%) diagnosed with cardioembolic stroke, 35 (46%) were females. Mean age was 53.5±12.2 years. Occurrence of cardioembolic stroke was seen to be higher (71% vs 28.9%, p value<0.0001) in patients of older age group (46 years or more). A significant proportion of patients of the older age group (37%) had hypertension (p value=0.0048). Coronary artery disease (CAD) was the most prevalent cardiac disorder, observed in 42 patients (55.2%), valvular heart disease in 22 patients (28.9%) and atrial fibrillation in 14 patients (18.4%). Limb weakness (84.2%) and Middle Cerebral Artery (MCA) territory (73.6%) infarct were observed in majority of the patients. Conclusions: Prevalence of cardioembolic stroke in this region is lower than reported worldwide. While male predominance of cardioembolic stroke was noted, old age and hypertension were the major vascular risk factors identified. CAD was the major source of cardioembolism.